PROMOTING STUDENTS’ AUTONOMOUS LEARNING THROUGH ENGLISH PRONUNCIATION APPLICATION IN LEARNING PRONUNCIATION - Dini Haryanti; R. Bunga Febriani; Didih Faridah (JALL (Journal of Applied Linguistics and Literacy), 2022)
This study presents the use of English Pronunciation application to promote students’ autonomous learning in learning pronunciation. This study is aimed to interpret students' perceptions towards the use of English Pronunciation application on their autonomous learning in learning pronunciation and to explore the use of English Pronunciation application in promoting students’ autonomous learning in learning pronunciation. A qualitative case study was applied as the research design of this study. The data were collected by using questionnaires and interviews. The participants were 30 students of the freshman of English Education Program in Galuh University. The result of this study showed that the use of English Pronunciation application in learning pronunciation is effective to promote students’ autonomous learning. Moreover, the students perceived that the use of English Pronunciation application in learning pronunciation can helps them in overcoming their problems in learning pronunciation. Besides, it makes them more motivated, feel better and confidence with their pronunciation and also can improve their pronunciation skills.Keywords: autonomous learning, English Pronunciation application, and pronunciation.